Osteopontin N-Terminal Function in an Abdominal Aortic Aneurysm From Apolipoprotein E-Deficient Mice - Liu, Hongyang; Zhang, Ying; Song, Wei; Sun, Yancui; Jiang, Yinong (Frontiers in Cell and Developmental Biology, 2021)
The cleavage of osteopontin (OPN) by thrombin results in an N-terminal fragment (OPN-N), which exposes a cryptic integrin-binding motif that promotes the adherence of cells, and plays a proinflammatory role. However, the effect of OPN-N on abdominal aortic aneurysm (AAA) remains unknown. The aim of this study was to investigate the expression of OPN-N in aortic tissue samples obtained from patients, who underwent acute aortic dissection (AD), and normal aorta, effect of OPN-N on angiotensin (Ang) II-induced AAA in mice, and relationship between OPN-N and pyroptosis-related inflammatory factors in vitro. Hematoxylin and eosin staining was conducted to detect histological changes. Next, we detected the expression of the OPN-N protein. Additionally, ApoE-/- mice were divided into four groups: control, control + M5Ab (to block the OPN-N function in mice), Ang II, and Ang II + M5Ab. All mice were euthanized after a 28-day infusion and whole aortas, including thoracic and abdominal aortas, were collected for morphological and histological analysis of the AAA. The OPN-N protein expression was higher in patients with AD than in normal individuals, while histological changes in the aortas of Ang II mice were suppressed in Ang II + M5Ab mice. The expression of OPN-N, NOD-, LRR-, and pyrin domain-containing protein 3, pro-Caspase-1, ASC, Gasdermin-d, interleukin (IL)-18, IL-1β, matrix metalloproteinase (MMP) 2, and MMP9 was lower in the Ang II + M5Ab group than that in the Ang II group. The gene expression of monocyte chemoattractant protein-1, IL-6, and tumor necrosis factor-α was suppressed in the aortic tissues of the Ang II + M5Ab group compared with the Ang II group. Moreover, the expression of α-smooth muscle actin was lower in the Ang II group than in the Ang II + M5Ab group. In vitro results showed that the increase in the expression of pyroptosis-related inflammatory factors induced by OPN was mediated through the nuclear factor (NF)-κB pathway. In conclusion, OPN-N promotes AAA by increasing the expression of pyroptosis-related inflammatory factors through the NF-κB pathway, inflammation, and extracellular matrix degradation. These results highlight the potential of OPN-N as a new therapeutic target to prevent AAA expansion.